Kajian pengaplikasian serat ketola dalam produk hiasan dalaman - Yuslina, binti Yahya (Universiti Malaysia Sarawak (UNIMAS), 2007)
The research presents the application of luffa fiber in interior design. Luffa fibrous is selected as the research material because the fiber remising better, stable and have remarkable texture. The main objective of the research is to manipulate the natural sour as of luffa fiber. Some techniques are used to manipulate the fiber like weaving, embroidery, patchwork and hot press to ensure look more sophisticated and beauty. Beside that the research is to studies the potential of luffa fiber as the new material in interior design product.